Left Bundle Branch Block and Complete Heart Block Complicating Inferior Myocardial Infarction. Issue 1 (13th July 2016) - Gruber, Jillian S.; Stair, Brad; Aktas, Mehmet; Bravo‐Jaimes, Katia
Abstract : Left bundle branch block following inferior myocardial infarction remains uncommon and scarcely reported in the literature. We describe a rare presentation of a 58‐year‐old male patient who developed left bundle branch block and third degree atrioventricular block after inferior myocardial infarction requiring permanent pacemaker placement. Pathophysiology, impact on mortality, and management options are discussed.